TGF-β1 regulating miR-205/miR-195 expression affects the TGF-β signal pathway by respectively targeting SMAD2/SMAD7 - Duan, Yingjun (Oncol Rep, 2016)
Transforming growth factor-β (TGF-β) proteins are important cytokines in the occurrence and development of tumors. However, its neural functions in glioma are still not understood. In the present study, we evaluated the effects of TGF-β1 on glioma cell line U87. miR-205 and miR-195 were involved in TGF-β1 signaling pathway. Quantitative real-time PCR was used to detect miR-205 and miR-195 levels in human glioma tissue samples and U87 cells treated with different concentrations of TGF-β1. Enzyme-linked immunosorbent assay (ELISA) was performed to determine TGF-β1 in the glioma patients peripheral blood. In vitro, U87 cells were transfected with mimics or inhibitors of miR-205 and miR-195. SMAD proteins were assayed by western blotting. Luciferase assay and co-immunoprecipitation (Co-IP) were used to determine the relationships between miR-205 and SMAD2, miR-195 and SMAD7. Effects of miR-205 and miR-195 on glioma cell proliferation and invasion using colony forming and cell migration assays. It was shown that miR-205 was decreased in glioma tissue, but miR-195 and TGF-β1 was increased. In addition, TGF-β1 concentration was negatively correlated with miR-205 mRNA level, but positively correlated with miR-195 mRNA. In addition, miR-205 was downregulated and miR-195 was upregulated by TGF-β1 in a dose-dependent manner. miR-205 and miR-195 targeted and inhibited SMAD2 and SMAD7 expression, respectively, in U87. High expression of miR-205 but not miR-195 reduced SMAD2 and SMAD4 heteromer formation. In addition, it was also shown that miR-205 overexpression inhibited U87 proliferation and invasion efficiently. All the results suggested that miR-205 and miR-195 participated in the TGF-β1 signaling pathway and showed opposite effects in glioma. These findings contribute to the understanding of TGF-β1 function in glioma.